Analysis of the use of online teaching tools in specific circumstances - Varga, Matija, informatičar (Array, 2020)
E-learning can be viewed from a technical and pedagogical aspect, so the application of e-learning in teaching requires ICT knowledge and skills and pedagogical competencies for the use of ICT in teaching. Work on the topic: "Analysis of the use of online teaching tools in specific circumstances" consists of two parts. The first part of the paper, which uses a scientific method of content analysis, presents types of online teaching tools in specific circumstances and explanations of online teaching tools in specific circumstances. Also, the advantages and disadvantages of the online learning tools (as well as the advantages and disadvantages of the LMS, i.e. learning management system) are described. The second part of the paper presents the research results obtained by the scientific method of interviewing. Based on the surveys, answers (results) were obtained to the nine questions asked. Hypotheses were set in the paper: Ht1 and Ha1 and Ht2 and Ha2. Based on the results obtained by interviewing the respondents (analysis of answers), the paper confirmed the basic hypotheses (Ht1 and Ht2), while the alternative hypotheses (Ha1 and Ha2) have been rejected.